Daryāft - Naishnal Yūnīvarsiṭī āf Māḍran Laingvejiz (Islāmābād, Pakistan) (Naishnal Yūnīvarsiṭī āf Māḍran Laingvejiz, 2002)
Articles on Urdu language and literature.
Keywords: Urdu language : Periodicals; Urdu language : Study and teaching : Pakistan : Periodicals; Urdu literature : Pakistan : History and criticism : Periodicals; Urdu language; Urdu language : Study and teaching; Urdu literature; Pakistan